Pengaruh Pemberian Wedang Jahe (Zingibear Officinale Var. Officinale) Terhadap Frekuensi Emesis Gravidarum Pada Ibu Hamil Trimester Pertama (Di Wilayah Kerja Puskesmas Keputih Surabaya) - Meiri, Eka; Kibas, Noviana (Sekolah Tinggi Ilmu Kesehatan Surabaya, 2017)
Pregnancy is a natural process, the changes that occur in women during normal pregnancy is physiological and not pathological. Complaints from pregnant women is nausea and vomiting (morning sickness). Nausea and vomiting in pregnancy is common, especially in the first trimester. In some pregnant women, nausea and vomiting that occurs in the first trimester can continue until the time of the birth. Nausea and vomiting that goes great, called with hyperemesis gravidarum, which can harm the mother and the fetus, because of the difficulty of nutrients to enter. The purpose of this study was to determine the effect of ginger is there to the frequency of morning sickness in the first trimester in Puskesmas Keputih Surabaya. This type of research used in this study is Quasi Experiment. The research design in this study using a study design One group pretest - Posstest Design. Populasi that all pregnant women the first trimester, while samples are 10 respondents. The instrument used was a questionnaire. The technique used to determine the effect of dependent and independent variables are test Statistics Wilcoxon test. Results of research conducted in Puskesmas Keputih Surabaya showed women who experience morning sickness after being given a decline in the frequency of ginger emesis gravidarum. From the statistical test result obtained Wilcoxon test p-value 0.004 <α (0.05). Conclusion the study is effect of ginger on the frequency of morning sickness in the first trimester in the region work of Puskesmas Keputih Surabaya. Threfore, we recommend that pregnant women experience morning sickness is recommended to consume ginger because apart reachable ginger is also inexpensive and have many benefits as well as ginger safe for consumption.